Estrategia de booklets para fortalecer el aprendizaje del idioma inglés en los alumnos del centro de idiomas de la Universidad Técnica de Babahoyo, 2022 - Franco Bayas, Miguel Andrés (2022)
The aim of this investigation was substantiated on the layout of a booklet strategy to boost the English language in the scholars of the Language Center of the Technical University of Babahoyo, which was born due to the repetitive didactic material that the students used when they received classes, therefore, the workbook will solve this problem and help the students to have a material related to a real context and guided by information and communication technologies. The estimated population for the development of this strategy was 120 students belonging to the Language Center. The type of research was applicative, mixed, descriptive and propositive. For this project, the survey technique was used in which a questionnaire of 18 closed questions was made using the Likert scale with five categories. It is concluded that this strategy facilitates the understanding of activities, has access to free content that allows strengthening language skills in this language; also, the integration of web technologies, video and artificial intelligence provide an added value to this material that will serve as a didactic guide to trainees when they receive their classes and especially for a virtual context.